The Impact of Hierarchy of Information and Ethical Predisposition on Aggressive Reporting - Ying Zhee, Lim; Che Azmi, Anna Azriati (Asian Journal of Accounting Perspectives, 2022)
Research aim: The objective of this study is to examine whether ethical predisposition and hierarchy of information can explain the aggressive reporting by managers. Design/methodology/approach: A 3×2 between-subjects experiment manipulating the hierarchy of information (principle, principle + criteria, and principle + criteria + indicators) and ethical predisposition (utilitarianism + formalistic) was conducted to examine their joint effect on managers’ decision making. Research Findings: Statistical results revealed that ethical predisposition influenced aggressive reporting in the presence of more levels in the hierarchy of information in accounting standards. Theoretical contribution/ Originality: This study proposes that in drafting accounting standards, standard setters should strike a balance in how much information is to be provided. Our study also provides evidence that accounting standards should not be too general or too specific. Moving towards either one of these two extremes could lead to undesired reporting patterns by accountants. Practitioner/ Policy implication: The findings of the study provide useful insights into how individuals’ attributes affect the interpretation of the different levels of hierarchy of information in accounting standards. The findings are beneficial for standard setters in drafting accounting standards. Research limitation: Owing to factors such as time limit and appropriate length of the instrument, the study had to exclude some specificity of the standard, such as definitions and descriptions of the standard, from the instrument. It is possible that the incomplete information might have influenced the participants in making their judgment. Besides, since accounting students who returned from practical training were used as proxies for chief finance officers (CFOs), the viewpoints or opinions on how the decision was made might not be in line with actual practice because they might not serve in a decision making capacity during the practical training. Keywords: Aggressive Reporting, Formalistic, Information Hierarchy, Utilitarian Type of article: Research Paper JEL Classification: M3